The Correspondence: The Order of Heavens and the Order of the Earth - BAZAC, Ana (Studia Universitatis Babeș-Bolyai Philosophia, 2025)
This epistemological paper may be thought of as a joke. Still, its aim is serious enough: to show the meanings of an almost taboo topic taken in its double metaphorical sense, indicated here by capital letters: relations between the Heaven(s) and the Earth. These meanings appear as a result of a “multi-disciplinary” philosophical approach that, far from confusing us, emphasises, first of all, the different criteria of approaching the relationship between the two “types” of order mentioned in the title. These criteria are metaphysical, epistemological, logical, linguistic, and historical. However, after shedding light on the outlooks these criteria open, the meanings, according to their common metaphorical understanding, appear to be more critical.